The Digital Dasein: The Signifier of the World and its Virtual Truth - de Barros Moon, Rodrigo Malcolm [UNESP]; Gobbi, Maria Cristina [UNESP] (Colegio Mayor de Nuestra Senora del Rosario, 2024)
Immersed in a chaotic sea of data, we are constantly searching for meaning in the information that reaches us, in order to guide our action and our thinking. Throughout history, we have produced increasingly sophisticated means of storing and transmitting information, from writing to 3D representation in computer graphics. Each device with its own language, program, and function. The natural consequence of this development is an ever-increasing and intense production and circulation of information, which requires new methods capable of filtering it so that we can grasp reality in its constitution. The analysis methodology is based on a theoretical review. Due to the multitude of issues that arise today, at the intersection between information and digital technology, we will focus on theories that can validate a sufficient reason to guide us these days. We will discuss the image as information: its ontology and methods of fabrication in order to understand its current state. Correlating the situation of the world (dasein) with the interpretation of images, the main problem of this article arises: how to use digital images to situate ourselves in today’s world?.
El dasein digital: el significante del mundo y su verdad virtual
DASEIN DIGITAL: O SIGNIFICANTE DE MUNDO E SUA VERDADE VIRTUAL
Keywords: dasein; digital image; Information; ontology; technology